Guanylyl cyclase/natriuretic peptide receptor-A: Identification, molecular characterization, and physiological genomics - Pandey, Kailash N. (Frontiers in Molecular Neuroscience, 2023)
The natriuretic peptides (NPs) hormone family, which consists mainly of atrial, brain, and C-type NPs (ANP, BNP, and CNP), play diverse roles in mammalian species, ranging from renal, cardiac, endocrine, neural, and vascular hemodynamics to metabolic regulations, immune responsiveness, and energy distributions. Over the last four decades, new data has transpired regarding the biochemical and molecular compositions, signaling mechanisms, and physiological and pathophysiological functions of NPs and their receptors. NPs are incremented mainly in eliciting natriuretic, diuretic, endocrine, vasodilatory, and neurological activities, along with antiproliferative, antimitogenic, antiinflammatory, and antifibrotic responses. The main locus responsible in the biological and physiological regulatory actions of NPs (ANP and BNP) is the plasma membrane guanylyl cyclase/natriuretic peptide receptor-A (GC-A/NPRA), a member of the growing multi-limbed GC family of receptors. Advances in this field have provided tremendous insights into the critical role of Npr1 (encoding GC-A/NPRA) in the reduction of fluid volume and blood pressure homeostasis, protection against renal and cardiac remodeling, and moderation and mediation of neurological disorders. The generation and use of genetically engineered animals, including gene-targeted (gene-knockout and gene-duplication) and transgenic mutant mouse models has revealed and clarified the varied roles and pleiotropic functions of GC-A/NPRA in vivo in intact animals. This review provides a chronological development of the biochemical, molecular, physiological, and pathophysiological functions of GC-A/NPRA, including signaling pathways, genomics, and gene regulation in both normal and disease states.